Burden of Illness in Prostate Cancer Patients with a Low-to-Moderate Risk of Progression: A One-Year, Pan-European Observational Study. (13th March 2014) - Selli, Cesare; Bjartell, Anders; Burgos, Javier; Somerville, Matthew; Palacios, Juan-Manuel; Benjamin, Laure; Black, Libby; Castro, Ramiro
Abstract : Objective . To assess the impact of low-to-moderate risk prostate cancer on patients' quality of life (QoL) at diagnosis and within the first year of treatment. Subjects and Methods . Men (n = 672 ) aged 50–75 years with prostate cancer (Gleason score ≤ 7, PSA ≤ 20  ng/mL and clinical staging T1c–T2b) were enrolled in five European countries. Patients completed five questionnaires, including EORTC Quality of Life Questionnaire—Prostate Cancer 25 (QLQ-PR25) and EORTC Quality of Life Questionnaire—Cancer 30 (QLQ-C30). Questionnaires were completed at baseline, at 3 months and 12 months after starting treatment. The primary endpoint was the change in QLQ-PR25 urinary symptoms subscale score from baseline to the assessment at 3 months. Results . Mean (SD) age was 65.0 (5.7) years and 400 (66%) men had Gleason score ≤6 prostate cancer. The most frequently used initial treatment was radical prostatectomy (71% of patients). QLQ-PR25 urinary symptoms subscale score was significantly increased at 3 months (P < 0.001 ), indicating that urinary symptoms worsened after treatment. The score was lower at 12 months than at 3 months, but it was still significantly higher than at baseline (P < 0.001 ). Hormonal treatment-related symptoms, sexual functioning, and sexual activity scores significantly worsened at 3 and 12 months (all P < 0.001 ). For the QLQ-C30 questionnaire, global health status/QoL score significantly decreased at month 3 but was not different from baseline by month 12. Scales for physical, role, and social functioning, and fatigue, showed significant deterioration at 3 and 12 months. Conclusions . Low-to-moderate risk prostate cancer may have a substantial effect on patients' QoL within one year following treatment.